Enhancing profitability of oil palm based cropping system through resource use efficient technologies with farmer-scientist and stakeholders interface - Prasad, M V; Manorama, K; Suresh, K; Rao, B N; Mathur, R K; Rajesh, K; Mahesh, S S N M; Srikanth, K; Harinarayana, P; Ambika, K Lakshmi (Indian Farming, 2022)
.